2014
DOI: 10.3892/etm.2014.1803
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis and etiology of porokeratosis

Abstract: The present study was performed in order to define the clinical manifestations of porokeratosis, with particular emphasis on genital porokeratosis. A total of 55 cases of porokeratosis were retrospectively reviewed between 2000 and 2007 from Huashan Hospital (Shanghai, China). Out of 55 cases, there were 22 cases of porokeratosis of Mibelli, 17 cases of disseminated superficial actinic porokeratosis (DSAP), 15 cases of disseminated superficial porokeratosis and one case of linear porokeratosis. The ratio of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 33 publications
(34 reference statements)
0
20
0
11
Order By: Relevance
“…En sık PM ve DSAP klinik tipleri görülmektedir. 1,5 İnsidansı tam olarak bilinmeyen hastalık, dünyanın her yerinde saptanabilmektedir. 2,4 Porokeratoz her iki cinsiyeti de etkileyebilmekle birlikte, daha sıklıkla erkeklere tesir eden bir hastalıktır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En sık PM ve DSAP klinik tipleri görülmektedir. 1,5 İnsidansı tam olarak bilinmeyen hastalık, dünyanın her yerinde saptanabilmektedir. 2,4 Porokeratoz her iki cinsiyeti de etkileyebilmekle birlikte, daha sıklıkla erkeklere tesir eden bir hastalıktır.…”
Section: Discussionunclassified
“…2,4 Porokeratoz her iki cinsiyeti de etkileyebilmekle birlikte, daha sıklıkla erkeklere tesir eden bir hastalıktır. 2,3,5 PM daha çok erkeklerde, DSAP ise daha çok kadınlarda görülmektedir. 4,5 PM' de lezyonlar aktinik formlar ile karşılaştırıldığında daha erken yaşlarda başlamaktadır.…”
Section: Discussionunclassified
“…The most effective treatments for disseminated forms of porokeratosis include topical 5‐fluorouracil, topical retinoids, and topical vitamin D3 analogues . However, for isolated forms, as in this case, the definitive treatment is surgical excision; a retrospective review of seven patients with genital porokeratosis showed no recurrence after 7 years of follow‐up …”
mentioning
confidence: 88%
“…There are familial variants that are thought to be autosomal dominant . The predominant symptom is pruritus . Morphologically lesions are characterized by atrophic, spreading, annular patches, surrounded by a ridged hyperkeratotic border…”
mentioning
confidence: 99%
“…Education regarding sun protection and regular checks for malignant conditions is needed in patients with DSAP as all of the clinical variants of porokeratosis have the potential for malignant transformation with an overall incidence of 7.5% to 11% [3,5].…”
Section: Sirmentioning
confidence: 99%